Meloxicam Carbopol-Based Gels: Characterization and Evaluation - Sareen, Rashmi; Kumar, Sandeep; D. Gupta, G. (Current Drug Delivery, 2011)
Purpose: To formulate and evaluate the hydrogels containing meloxicam for topical application and also compare the effect of penetration enhancers on release of drug. Methods: Meloxicam gels were prepared by dispersion method using carbopol-940 and 934 (1%w/w) as rate controlling polymer and drug penetration enhancers such as tween 80, oleic acid and sesame oil in the concentration of 1% and 2% . The formulated gels were evaluated for drug content, pH, viscosity, spreadability, extrudability, in vitro drug permeation, drug release kinetics, bioadhesion test, accelerated stability of selected gel formulation. The in vitro drug permeation through pig's skin was carried out by using Keshary-Chein diffusion cell and viscosity was determined by brookfield viscometer (Modle No. LVDVE). Results: All the gel formulations were found to be very clear and homogeneous. Drug content of all formulations was found to be above 93%. Formulation F14 containing carbopol-934(1%w/w) and sesame oil 2% gave 99% release as compared to other formulations obeying zero order kinetic with a good bioadhesion quality. The permeability coefficient of all formulations was found in the range of 0.2 to 0.4 × 10-3cm2/hr. The results were compared statistically and found with satisfactory correlation and it was observed that the rate of drug release increased with increase in concentration of penetration enhancers.
Keywords: arthritic conditions